Harnessing parent power: to what extent can parental engagement enhance the development of growth mindset in secondary school children? - Battison, A (2016)
This study has focussed on how parental engagement can be used as an intervention to develop a growth mindset in young adolescent boys. The research frame has been a case study approach designed to gather data that is rich enough to analyse a mediated act as complex as parenting. Therefore, the methods have been mixed and varied to enable thorough triangulation and have included semi-structured interviews, questionnaires, diaries, informal observation, drawing and pictures. The intervention period itself lasted six months. The context is set within a co-educational, fee paying, independent boarding school which is non-selective and provides bursarial assistance to those from lower socio-economic backgrounds; four local day boys in year 9 were randomly selected from a targeted group as the case study students. Many schools involve parents via emails and newsletters, reports and parents’ evenings, all of which serve to relay information in a useful and important way. However, in a complex and ever changing world I propose that schools must get more creative to strengthen the learning culture around each child. Parental participation in schools, particularly parental engagement (where parents are empowered to further develop their child’s learning dispositions at home) can have huge effects on that child’s lifetime achievement. All students developed a more incremental mindset as a result of the parental intervention albeit to varying degrees. The main factors that influenced the degree of progress were upheaval within the family unit and how the strategies we employed by the parents. Unsurprisingly, I found that parents experience responsible parenting to be challenging, and that they were very grateful for support and guidance. Providing autonomy was found to be an important factor in successful strategies with the young adolescents, as was working in a careful manner via questioning, using process oriented praise and collaborative, learning-orientated, goal setting; all of which were best deployed in a light-touch manner. The project sat within a whole school initiative to engage pupils, teachers and parents in strategies to develop learner self-sufficiency, as part of a collective culture, within a community of learning. The process and reflections of all involved within this project will help to develop our continued focus on a wholeness approach and continue to dissolve the boundaries between the silos of traditional educational practice and perceived responsibility.